The Urgency of Social Competency of PAI Teachers in Handling Conflict: Win Win Solutions in Reaching Religious Harmony - Mahrudin Mahrudin (Didaktika Religia, 2017)
The existence of teachers in the community can be a role model as well as referrals around the community. In establishing harmony as well as interreligious harmony, PAI teachers have a very big role in the community. Their status as religious figures demands them to act as saints who become role model in attitude and behavior. They are to be able to protect and serve the community regardless religious differences in adherents by the community itself.